The manuscript and print contexts of older Scots romance - Wingfield, E (2010)
This thesis is a study of the fifteenth- and sixteenth-century manuscript and print contexts of Older Scots romance. Building on recent developments in Middle English romance scholarship and Older Scots book history, it seeks to contextualise the surviving corpus of Older Scots romances in light of their unique material witnesses and contemporary cultural milieu. Chapters 1 to 8 focus respectively on the following Older Scots romances: the Octosyllabic Alexander, the Buik of King Alexander the Conquerour, Florimond, Lancelot of the Laik, King Orphius and Sir Colling, Golagros and Gawane and Rauf Coilȝear, the Scottish Troy Book, and Clariodus. The conclusion assesses and evaluates the most significant and recurring features of these chapters and reveals how they cumulatively deepen our understanding of the book-producing and book-owning culture of fifteenth- and sixteenth-century Scotland. The conclusion also looks forward to new witness- conscious editions of Older Scots romance that endeavour to represent as far as possible a text’s unique and idiosyncratic manuscript and print contexts.   In each chapter I examine the set romance’s primary contexts of composition, including authorship, date, and first audience, as well as its secondary publication contexts. A full palaeographical, codicological and bibliographical description of each manuscript and print is provided, with details of when, where and by whom each witness was produced. Information about when and where that witness was read is also given, with details of the owners and readers where known. Significant attention is paid to the use of titles, rubrication and mise-en-page to reveal the trends and bibliographical codes in copying and presentation. Where appropriate, the compilation choices made by scribes and readers are also analysed. Careful assessments of these are shown to aid modern thematic and comparative literary interpretation. Most notably, each chapter of this thesis also provides much-needed new information about fifteenth- and sixteenth-century Scottish literary communities. Several significant and often-overlapping circles of scribes, readers and owners are revealed. The familial, professional and geographical associations between these groups of producers and consumers are traced and consequently new book- publishing and book-owning networks are documented. In further original work, a number of hitherto unknown texts, scribes and readers are also successfully identified.